Green Nanocatalysts From Biomass For Sustainable Biodiesel Production From Used Cooking Oil (UIR PRESS, 2025)
This study presents the development of an in-house sustainable nanocatalyst derived from rice husk and sugarcane bagasse for biodiesel production from used cooking oil. The esterification and transesterification processes were carried out to convert triglycerides in the used cooking oil into fatty acid methyl ester (FAME). The biocomposite nanocatalyst produced had a particle size of 2.5 nm. The results showed that the highest biodiesel conversion yield achieved was 97.7%, under optimal operating parameters: a methanol-to-oil ratio (MTOR) of 12:1, a catalyst dosage of 6%, a temperature of 65°C, and a reaction time of 75 minutes. This catalyst demonstrated a higher conversion yield compared to similar green catalysts. Furthermore, the quality of the biodiesel produced conformed to the Indonesian National Standard SNI 7182:2005